Konfrontacje rosyjsko-polskie w dramatach Gabrieli Zapolskiej - Mazurek, Halina (Acta Polono-Ruthenica, 2018)
In the article were subjected analysis and interpretation three dramas of the writer, treating about Russian-Polish relationships under the annexation. Zapolska broke in them stereotypes in portraying mutual relations Poles and Russians. Hostile reposition marked mostly the representati- ves of the tsarist power. It was returned by Poles. However usual people looked for agreements. The contribution of Zapolska was also creation of the Russian gendarme figure about human features, which in the face of Poles tried not to be cruel and unfair. Russian-Polish confrontations reflecting in dialogues of the representatives of both nations are the determinant of the dramaturgy of Zapolska arts, steer the run of the action, proclaim in itself dramas in the drama, because the main intrigue is holds beyond the scene.